Os limites do conhecimento nas Diretrizes Curriculares Nacionais do Curso de Graduação em Farmácia: um estudo a partir da ontologia marxiana - Lopes, Adriano Jorge Torres (2012)
The dissertative text which now is brought to light deals, in stricto sensu, with the philosophical-scientific investigation about the knowledge in the national curricular guidelines of the graduation course in Pharmacy (DCNF) and its limits, submiting such category to the precision of the marxian ontology. By its time, in lato sensu, the research brings to sight the importance of carrying out a study paved on material bases, guided by the incessant ontohistorical approximation to the studied object. The textual systematization is divided into two chapters which own relative independence, although they have a historical sense of ontological determination. The initial chapter is intended for to provide base to the grounding of what the knowledge is, or, in other terms, its genesis and function. This way, the concrete abstractions of Marx’s philosophy (in his writings until 1850) and Lukács (in his texts about the Ontology of the social being) were put vis-à-vis to the scientific discoveries of the current paleoanthropology, aiming not to defend gnosiologically the thought of some author in particular, but to unveil (ontologically) the self object. Consequently, both philosophical categories and scientific categories (teleology, causality, bipedalism-tecnology-brainincreased size, specialized and non-specialized) were studied, into being analyzed in their interface between the biological-causal and the historical-cultural; from the ontological bound of natural being (organic and inorganic) to social being, unveiling the proper place of (ontological) importance of the knowledge with reference to the labor. In the last chapter, the critical comparison of the notion of knowledge of the DCNF with reference to the ontohistorically grounded knowledge was done. Under this management, referential dedicated to the research in pharmaceutical education of several theoretical orientation was used.